Association of Root and Leaf Silicon Application Decreases the C/Si Ratio, Increasing Carbon Gain and Dry Mass Production in Peanut Plants - Fernandes, Stefania [UNESP]; Pereira Da Silva, Gilmara; Prado, Renato De Mello [UNESP]; Rossatto, Davi Rodrigo [UNESP] (Taylor & Francis Inc, 2021)
Silicon (Si), depending on the application method, can benefit the growth of peanuts by stoichiometric modification of carbon (C); however, this is not yet well known in this culture. Therefore, the objective was to evaluate whether different application forms of Si increases the growth of peanut plants due to stoichiometric changes C/Si and consequently stomatal conductance and photosynthesis. The experiment was carried out in a greenhouse in pots with nutrient solution using peanut plants cultivating granoleic. The treatments were: control, without Si application (-Si); Si via root (Si R) (2.0 mmol L-1) Si via leaf (Si F) (4.0 mmol L-1) and Si via root associated with leaf (Si R + F), arranged in randomized blocks with five repetitions. The variables analyzed were: Si content and accumulation, carbon percentage, C/Si ratio, efficiency of C use, photosynthesis, stomatal conductance, transpiration, dry matter and productivity. The application of root Si plus leaf spray is efficient to increase the accumulation of the element in the aerial part of the peanut. The benefit of Si in the growth of peanut plants is due to its effect of modifying the stoichiometric C/Si ratio in the plant, which resulted in an increase in the photosynthetic rate and, consequently, in the efficiency of the use of C and the production of dry matter and productivity of the plant.
Keywords: Arachis hypogaea l; beneficial elemento; forms application; stoichiometric relationship